Diasporic Palestinian Communities in Brazil and Hierarchies of Belonging - Munem, Bahia M.; Hamid, Sônia Cristina (Revista Territórios e Fronteiras, 2021)
In this article, we examine the historical migration of Palestinians to Brazil, while also exploring the resettlement of a group of just over 100 Palestinian refugees in the country. We seek to focus on this group to attend to specificities in the migratory designations of immigrant and refugee and the complex ways these are activated, their gendered-class formation and distinctions, and important nuances in the overarching category “Arab” (or “turco” or “Sírio-Libanês”) in which differences are subsumed and particularities flattened. Neste artigo, examinamos a histórica migração de palestinos para o Brasil e exploramos o reassentamento de um grupo de pouco mais de 100 refugiados palestinos no país. Focamos nestes grupos com o intuito de entender as especificidades das designações migratórias de imigrantes e refugiados e o modo como são acionadas; suas formações e distinções de classe e gênero; e as nuances existentes na abrangente categoria “árabe” (“turco” ou “sírio-libanês”), a partir da qual as diferenças e particularidades dos grupos não são consideradas.